751 Texting and walking: a controlled field study of crossing behaviours and inattentional blindness in Taiwan. (1st September 2016) - Pai, Chih-Wei
Abstract : Objective: The paper investigates the effects of phone use (talking, texting, and listening to music) on the street-crossing behaviours of pedestrians and their inattentional blindness in Taiwan. Background: Recent handsets with touchscreens, as well as more advanced features including multimedia, and mobile applications (apps), exacerbate problems relating to cognitive distraction and reduced situation awareness. Method: A controlled field study using video cameras was conducted for observing pedestrians crossing behaviours (e.g., crossing time, sudden stops, looking both ways before crossing, disobeying traffic signals). Pedestrians were classified into two groups: experimental group (talking, texting, listening to music) and control group (no phone use). Pedestrians' inattentional blindness was examined by evaluating whether they saw an unusual object (i.e., a clown) nearby. Results: The results indicate that the proportions of unsafe crossing behaviours (e.g., sudden stops, disobeying traffic signals, not looking both ways before crossing) were higher among distracted individuals and more pronounced among those using instant-messaging apps. These instant-message app users were the least likely to see the clown, and music listeners were the least likely to hear the horn that the clown was honking. Contributing factors to unsafe behaviours include being a student, having a phone screen of 5 in. or larger, and having un-limited 3G Internet access. Conclusions: Texting message via apps was the leading factor on unsafe crossing behaviours of pedestrians and their inattentional blindness.